Aid for Trade Effectiveness: Complementarities with Economic Integration - Mariana Vijil (Fondation pour les études et recherches sur le développement international (FERDI), 2013)
Developing countries are increasingly using regional integration as a main policy lever when pursuing a trade-led growth strategy, and today, 'deep' preferential trade agreements go beyond trade policy negotiations and cover trade facilitation issues. Since aid for trade (AfT) has been recognized as a powerful instrument for increasing developing countries' trade capacity by targeting internal trade costs, this paper tests whether complementarities exist between this type of aid and economic integration using a gravity model on panel data for the period 1995 to 2005. Results indicate that AfT, when combined with economic integration, has been effective in increasing trade flows. Both South-South and North-South trade flows have benefited and the combination of the two instruments has been particularly effective in expanding the South's exports to the North. Finally, when breaking down AfT into categories, assistance to trade-related institutions seems to generate the strongest complementarities with economic integration.
Keywords: F1; O19; O24; 330; "Aid for trade"; commerce